Pengaruh Variabel Determinan terhadap Struktur Modal dan Dampak Struktur Modal terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia). - Ni Nyoman Suli Asmara Yanti; Kusuma Ratnawati; Djumahir Djumahir (University of Merdeka Malang, 2018)
This study aims to analyze determinant variables of capital structure and impact of capital structure on firm value. The determinants of capital structure such as tangibility, profitability, non-debt tax shields, uniqueness, and shares price performance are used as independent variables. Capital structure and firm value are used as dependent variables. Data analysis in this research uses regression analysis. The samples are 62 manufacturing firms listed on Indonesian Stock Exchange from 2012 to 2016. The result shows : 1) tangibility has a positive and significant impact on capital structure; 2) profitability has a negative and significant impact on capital structure; 3) non-debt tax shields, uniqueness and shares price performance do not impact on capital structure; 4) capital structure has a negative and significant impact on firm value https://doi.org/10.26905/jmdk.v6i2.2210